The Impact of Sea Transportation On Environmental Health - Husna, Iksiroh El; Kholilah, Nenik; Sarifuddin, Sarifuddin; Wijinurhayati, Anissofiah Azise; Idayatma, Widya Putri (RSF Conference Series: Engineering and Technology, 2023)
Discharging untreated ballast water into harbor waters often contains pathogenic bacteria, posing a potential threat as pollutants to the environment and fishery products. This study assesses the bacteriological impact of ballast water disposal on harbor waters and fishery products. Comparative analyses, utilizing both morphological and molecular examinations, are conducted to determine the presence of pathogenic bacteria according to the BWM Convention standards. The findings of morphological research on ballast water, harbor waters, and captured fish reveal similarities in the types of pathogenic bacteria, specifically the presence of V. cholerae and E. coli bacteria. Similarly, the molecular examination confirms the presence of the same pathogenic bacteria in both water and ballast samples, namely V. harveyi and V. parahaemolyticus. Additionally, other pathogenic bacteria are identified in the ballast water, including V. fortis and V. alginolyticus. Notably, there is no evidence of V. cholerae bacteria contribution from the river. Applying the BWM Convention is crucial and requires the attention of stakeholders to safeguard the maritime environment.